Constructively Aligned Assessment: An Integral Approach to Translation Teaching and Learning - Veiga Díaz, María; García González, Marta (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2016)
For the last 15 years, higher education has dramatically changed in terms of its mission and modes of delivery, involving many changes in how teachers approach course design and implementation, mainly because the final aim of learning is no longer the transmission of knowledge but the acquisition of competences for professional practice that promote graduates’ employability. One of the most affected processes has been evaluation, insofar as assessing these competences requires using strategies beyond the mere evaluation of declarative knowledge. Traditionally, evaluating in translation degrees has been said to be based on continuous assessment. However, the meaning and implications of ‘continuous assessment’ and its relation to ‘formative’ and ‘final’ assessment have often been misinterpreted as revealed in the literature. In this paper, we analyse the most common misconceptions in higher education assessment and, particularly, in translation teaching and learning. Furthermore, we present constructive alignment as a solid pedagogical framework for use in this field. Combining several formative methods and instruments is found to be most beneficial after reviewing the methods and instruments available and measuring the extent to which the intended learning outcomes were achieved as well as spotting individual learners’ needs. This paper emphasises the usefulness of continuous formative assessment as compared to continuous summative assessment, which measures the results of learning but does not act on the learning process.